Large fetal weight alone in Robson-1 parturients doesn't translate into a risk of Caesarean delivery higher then that of a vaginal birth. (August 2019) - Póka, Robert; Barna, Levente; Damjanovich, Péter; Farkas, Zsolt; Molnár, Szabolcs; Orosz, Mónika; Ördög, Lilla; Sipos, Attila; Juhász, Gábor; Török, Olga
Abstract: Objective: The authors analysed the Caesarean section rate as a function of birth weight among Robson-1 parturients and compared with that among the unselected obstetric population. Study design: A retrospective analysis of birth weight, maternal height and the route of delivery was carried out in an unselected obstetric population of 26, 012 parturients. The authors compared birth weight centile distributions of vaginally, and that of abdominally delivered fetuses between Robson-1 parturients as well as those of the total obstetric population. Results: The 90th birth weight centile of fetuses delivered at 37, 38, 39, 40, 41, and 42 weeks gestation were 3960 g, 3960 g, 4000 g, 3950 g, 4000 g and 3820 g, respectively. Among Robson-1 parturients, 677 fetuses weighed >4000 g, and 448 patients (66%) were delivered vaginally. Maternal height did not influence either the birth-weight-percentiles or the Caesarean-rates substantially. Above the birth weight of 4000 g, the Caesarean-rate among Robson-1 parturient rose similarly to that of the total obstetric population. In the knowledge of the most accurately estimated fetal weight, the odds of Caesarean delivery among Robson-1 parturients was not different from that of the total obstetric population. Among pregnancies with fetuses weighing less than 5000 g, the Caesarean-rate was below 50% in both Robson-1 parturients and the total obstetric population of 10 years. Conclusion: Even the best possible estimation of fetal weight cannot give a valid reason to downplay the intent of vaginal birth based on the fetal size above 3900 g that would be associated with increased odds of Caesarean delivery.